SOCIETAL MULTILINGUALISM (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
Societal multilingualism is a linguistic phenomenon where multiple languages coexist within a given society. This study explores the factors influencing societal multilingualism, its effects on cultural identity, and policy implications. Using a qualitative research approach, data from multilingual societies were analyzed to understand language dynamics and policy effectiveness.